2017
DOI: 10.1159/000455980
|View full text |Cite
|
Sign up to set email alerts
|

Expression Changes of Long Noncoding RNA in the Process of Endothelial Cell Activation

Abstract: Background: Endothelial cells have been shown to be in response to a variety of local and systemic stimuli, and are able to transition between quiescent and activated states. Endothelial cell activation is critical for the pathogenesis of various cardiovascular diseases. However, the expression changes of long non-coding RNAs (lncRNAs) are still unknown in the process of endothelial cell activation. Thus, this study was aimed to investigate expression changes of lncRNA before and after endothelial cell activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The expression of ~1900 lncRNAs was altered upon ox-LDL exposure in ECs, with CLDN10-AS1 and CTC-459I6.1 being the most regulated 90 . In a human model of EC activation induced by peripheral venous congestion, 27 lncRNAs were upregulated and 1 was downregulated 91 .…”
Section: Lncrnas In Vascular Diseasementioning
confidence: 99%
“…The expression of ~1900 lncRNAs was altered upon ox-LDL exposure in ECs, with CLDN10-AS1 and CTC-459I6.1 being the most regulated 90 . In a human model of EC activation induced by peripheral venous congestion, 27 lncRNAs were upregulated and 1 was downregulated 91 .…”
Section: Lncrnas In Vascular Diseasementioning
confidence: 99%
“…Our results showed that the lncRNA and mRNA expression results determined by microarray analysis had good reliability and reproducibility. LPS successfully activated HPMECs because the expression of SELE, IL-8, VCAM-1, CCL20 and ICAM-1 increased significantly in the experimental model [45][46][47]. In addition, GO and KEGG pathway enrichment analyses also suggested that the differentially expressed mRNAs participated in pulmonary endothelial inflammation and barrier dysfunction.…”
Section: Discussionmentioning
confidence: 94%